PENGARUH TINGKAT INFLASI, SUKU BUNGA DAN NILAI TUKAR RUPIAH TERHADAP RETURN SAHAM SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Suidarma Made (Jurnal Ilmiah Akuntansi & Bisnis, 2016)
This study aims to determine the effect of the independent variable is the rate of inflation, interest rates and the rupiah exchange rate partially to the return of Islamic stocks listed on the Stock Exchange Indoneisa, and also to determine the effect on stock returns syariah simultaneously listed on the Stock Exchange Indoneisa. This study uses multiple regression analysis, correlation, determination, t test and f. This study is quantitative in that it refers to the calculation of research data in the form of numbers. The variables of the study include independent and dependent variables. The sample in this study is the Jakarta Islamic Index (JII), which has 30 companies in it.The results showed that the inflation rate significant negative effect on stock return of syariah. SBI significant negative effect on stock return of syariah. The Rupiah significant negative effect on stock return of syariah. Simultaneously showed that the rate of inflation, interest rates and the rupiah significant positive effect on stock return of syariah.